Hysteresis of Electronic Transport in Graphene Transistors - Wang, Haomin; Wu, Yihong; Cong, Chunxiao; Shang, Jingzhi; Yu, Ting (ACS nano, 2010)
Graphene field effect transistors commonly comprise graphene flakes lying on SiO2 surfaces. The gate-voltage dependent conductance shows hysteresis depending on the gate sweeping rate/range. It is shown here that the transistors exhibit two different kinds of hysteresis in their electrical characteristics. Charge transfer causes a positive shift in the gate voltage of the minimum conductance, while capacitive gating can cause the negative shift of conductance with respect to gate voltage. The positive hysteretic phenomena decay with an increase of the number of layers in graphene flakes. Self-heating in a helium atmosphere significantly removes adsorbates and reduces positive hysteresis. We also observed negative hysteresis in graphene devices at low temperature. It is also found that an ice layer on/under graphene has a much stronger dipole moment than a water layer does. Mobile ions in the electrolyte gate and a polarity switch in the ferroelectric gate could also cause negative hysteresis in graphene transistors. These findings improved our understanding of the electrical response of graphene to its surroundings. The unique sensitivity to environment and related phenomena in graphene deserve further studies on nonvolatile memory, electrostatic detection, and chemically driven applications.